The availability of astaxanthin from shrimp shell wastes through microbial fermentations, Aeromonas hydrophila and cell disruptions - Cheong, Jee Yin; Abd Aziz, Nor Azwady; Go, Rusea; Ulul Azmi, Noormasshela; Abdul Ghafar, Nurul Shaziera; Ahmad Adli, Azleen; Mustafa, Muskhazli (Friends Science Publishers, 2014)
The removal of chitin and protein is crucial for the extraction of astaxanthin from shrimp shells. While the traditional method uses chemical extraction, the current study emphasises on the use of microbial enzyme, which is safer for the environment throughout the extraction process. Aeromonas hydrophila was isolated from shrimp shells and four types of sources were chosen; shrimp crab shell powder (SCSP), nitrogen sources, inorganic salts and carbon sources for the optimization of A. hydrophila culture media. Four types of cell disruption were introduced; autoclaving with distilled water, autolysis, heating and grinding with liquid nitrogen to further expose astaxanthin. The optimized culture media was found to be 7% SCSP, 9% bacto-peptone, 1% sodium chloride and 1% lactose at pH 7.0. This optimized media gave a high increment to both chitinase and protease activity from 0.092 and 60.816 U/mL to 1.164 and 272.565 U/mL, respectively. Mechanical cell disruptions using liquid nitrogen on pre-treated shrimp shells gave an astaxanthin recovery of 66% compared to the control. The availability of astaxanthin was made possible by the effects of optimization of the culture media in addition of mechanical cell disruptions.